Radiative properties of the first galaxies: Rapid transition from blue to red. Issue Volume 15:Issue S341(2019) (November 2019) - Arata, Shohei; Yajima, Hidenobu; Nagamine, Kentaro; Li, Yuexing; Khochfar, Sadegh
Abstract: Combining cosmological hydrodynamic simulations and radiative transfer (RT) calculations, we present predictions of multi-wavelength radiative properties of the first galaxies at z ∼ 6–5. We find that intermittent star formation due to supernova (SN) feedback causes the escape fraction of UV photons to fluctuate rapidly, which then produces the observed diversity of SEDs for high- z galaxies. The simulated galaxies make rapid transition between UV-bright and IR-bright phase, and our RT calculations suggest that dust temperatures in the first galaxies are higher than z < 3 galaxies with ∼ 60 K.